Long‐term variability in the water budget and its controls in an oak‐dominated temperate forest. Issue 25 (21st November 2013) - Xie, Jing; Sun, Ge; Chu, Hou‐Sen; Liu, Junguo; McNulty, Steven G.; Noormets, Asko; John, Ranjeet; Ouyang, Zutao; Zha, Tianshan; Li, Haitao; Guan, Wenbin; Chen, Jiquan
Abstract Water availability is one of the key environmental factors that control ecosystem functions in temperate forests. Changing climate is likely to alter the ecohydrology and other ecosystem processes, which affect forest structures and functions. We constructed a multi‐year water budget (2004–2010) and quantified environmental controls on an evapotranspiration (ET) in a 70‐year‐old mixed‐oak woodland forest in northwest Ohio, USA. ET was measured using the eddy‐covariance technique along with precipitation (P), soil volumetric water content (VWC), and shallow groundwater table fluctuation. Three biophysical models were constructed and validated to calculate potential ET (PET) for developing predictive monthly ET models. We found that the annual variability in ET was relatively stable and ranged from 578 mm in 2009 to 670 mm in 2010. In contrast, ET/P was more variable and ranged from 0.60 in 2006 to 0.96 in 2010. Mean annual ET/PET_FAO was 0.64, whereas the mean annual PET_FAO/P was 1.15. Annual ET/PET_FAO was relatively stable and ranged from 0.60 in 2005 to 0.72 in 2004. Soil water storage and shallow groundwater recharge during the non‐growing season were essential in supplying ET during the growing season when ET exceeded P. Spring leaf area index (LAI), summer photosynthetically active radiation, and autumn and winter air temperatures (Ta) were the most significant controls of monthly ET. Moreover, LAI regulated ET during the whole growing season and higher temperatures increased ET even during dry periods. Our empirical modelling showed that the interaction of LAI and PET explained >90% of the variability in measured ET. Altogether, we found that increases in Ta and shifts in P distribution are likely to impact forest hydrology by altering shallow groundwater fluctuations, soil water storage, and ET and, consequently, alter the ecosystem functions of temperate forests. Copyright © 2013 John Wiley & Sons, Ltd.